RELATIONSHIP BETWEEN FRENCH ANTI-COVID-19 “VACCINATION OPINION” AND PRINT MEDIA PUBLICATIONS - CALVAS, Patrick (MEDECINE LEGALE DROIT MEDICAL, 2025)
Vaccine reluctance is well established by various studies in the French population. Numerous complex and intertwining factors are known to influence individual attitudes. We compared the vaccination intentions of the French between the announcement of the vaccine development in July 2020 and the achievement of the full capacity of the vaccine resources in April 2021 and studied how the vaccination intentions evolved within the same period. We highlight a correlation between the publications of the national written press and the month-by-month fluctuation of vaccination intentions. People’s opinion appears slightly out of step with the publications that precedes and clearly influences the upcoming polls. This strongly suggest an influence of the press on opinion. In addition, the content of the articles brings into play the multiple determinants of vaccine intentions. The way that decisive facts are extracted form the scientific literature and the manner that they are exposed in the daily and weekly articles demonstrates the diffusion and convergence of ideas between the press and the public opinion. It is noteworthy that the clarity and transparency of the press articles which evolves with the time is possibly one of the important actors of the adhesion of the citizens to the anti-Covid-19 vaccination before any implementation of a policy of constraint by the authorities.